Pengaruh Model Pembelajaran PAKEM Terhadap Kemampuan Menulis Teks Eksplanasi Siswa - Sry Sarah Emita Sipayung (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This study aims to determine the effect of the PAKEM learning model on the ability to write explanatory texts for VIII students of SMP Negeri 1 Delitua in the 2022/2023 academic year. The sample in this study were 32 students of class VIII-1. The method used in this research is the one-group pre-test post-test design experimental method. Data analysis techniques in this study used analysis requirements test, normality test, homogeneity test and hypothesis test. The results showed that students' ability to write explanatory texts before using the PAKEM learning model was in the poor category with an average score of 63.34, while students' ability to write explanatory texts after using the PAKEM learning model was in the good category with an average score of 83. 84. The hypothesis test shows tcount > ttable, namely 11.3 > 2.039, then the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This shows that the use of the PAKEM learning model has a significant effect on the ability to write explanatory texts for class VIII students of SMP Negeri 1 Delitua in the 2022/2023 academic year.